1988
DOI: 10.1111/j.1460-2695.1988.tb01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Closure of Short Fatigue Cracks at Notches Under Compressive Mean Stresses

Abstract: Single-edge-notched specimens of a low-carbon steel were fatigued under cyclic in-plane bending with compressive mean stresses. The development of crack closure with crack growth was studied both experimentally and theoretically. The relation between the crack opening stress and the crack length was a function of the minimum (compressive) applied stress, irrespective of the maximum stress. The efl-ective stress intensity range was a unique parameter in correlating the crack growth rate, even if the crack wdS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This agreed with the fact that the crack initiated from the region R u of the bolt under-head that was opposite to the weld bead side in the full-circled sample as shown in Figure 5, because the cracks generate and propagate preferentially from the tensile side but not from the compressive side. 7,15,16 Accordingly, the strength decrease of 15% of the full-circled sample comparing with the bolt-only sample was mainly due to the tensile residual stress in the bolt under-head, because their fracture mechanisms were comparable as mentioned in the above section.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This agreed with the fact that the crack initiated from the region R u of the bolt under-head that was opposite to the weld bead side in the full-circled sample as shown in Figure 5, because the cracks generate and propagate preferentially from the tensile side but not from the compressive side. 7,15,16 Accordingly, the strength decrease of 15% of the full-circled sample comparing with the bolt-only sample was mainly due to the tensile residual stress in the bolt under-head, because their fracture mechanisms were comparable as mentioned in the above section.…”
Section: Resultsmentioning
confidence: 70%
“…The crack initiated from the right as well, but the propagated distance was shorter and is presumed to have met with the crack that propagated from the left and reached breakage at point F. From the beach marks and the distance to the point F, the left side was the first starting point of the crack and the right side was the second. 11,15…”
Section: Resultsmentioning
confidence: 99%
“…where the test constant C and even the exponent m might be dependent on mean stress or stress ratio. Equation (6) in fact is only a mathematical expression of the linear part of a S-N curve, as it is illustrated in Figure 4. It cannot be applied to cases that the stress amplitude is near the fatigue limit, and more inconveniently, constants C, m have to be determined individually by a large number of tests under the corresponding mean stress or stress ratio state.…”
Section: Life Formula For Tensile Mean Stress Statesmentioning
confidence: 99%
“…Generally, with the increase of tensile mean stress, both the fatigue limit and life would decrease rapidly. On the effect of compressive mean stress, some empirical expressions of fatigue limit and life-based on test results [5][6][7][8][9] can also be found. It has been found that fatigue limit increases with the absolute value of compressive mean stress [10][11][12][13], but it cannot be predicted at all by the well-known empirical formulas such as Goodman's or Gerber's relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In the calculation, the model is infinite plate. The experimental results agree well with the solid curve.When the measured residual stress is approximated by appropriate functions, the crack opening SIF can be calculated[9].…”
mentioning
confidence: 99%